2011
DOI: 10.1007/s10499-011-9482-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary propolis supplementation on growth performance, immune responses, disease resistance and body composition of juvenile eel, Anguilla japonica

Abstract: This study was conducted to investigate the effects of dietary propolis supplementation on growth performance, immune responses, disease resistance and body composition of juvenile eel, Anguilla japonica, in order to evaluate its bioavailability as a feed additive for this species. A total of 540 fish averaging 7.7 ± 0.22 g (mean ± SD) were randomly distributed into 18 tanks in groups of 30, and each tank was then randomly assigned to one of three replicates of six diets containing 0 (P 0 ), 0.25 (P 0.25 ), 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 27 publications
5
35
0
1
Order By: Relevance
“…To our knowledge, there is no available information on the effects of dietary Macsumsuk ® on haematological parameters of fish species. Similarly, the obtained results in HCT concerning the effect of Macsumsuk ® are supported by the findings of some researchers such as Bae et al (2012) who showed that HCT concentration of the juvenile eel, Anguilla japonica, decreased above the optimum level of dietary Propolis.…”
Section: Discussionsupporting
confidence: 82%
“…To our knowledge, there is no available information on the effects of dietary Macsumsuk ® on haematological parameters of fish species. Similarly, the obtained results in HCT concerning the effect of Macsumsuk ® are supported by the findings of some researchers such as Bae et al (2012) who showed that HCT concentration of the juvenile eel, Anguilla japonica, decreased above the optimum level of dietary Propolis.…”
Section: Discussionsupporting
confidence: 82%
“…; Bae et al . ). Likewise, results from the challenge test clarified a better physiological condition thereby health for rainbow trout fed dietary yellow loess compared to control diet and similar with oxytetracycline.…”
Section: Discussionmentioning
confidence: 97%
“…Similar observations have been reported in various previous studies for dietary additives such as propolis (Bae et al . ), green tea extract (Hwang et al . ) and onion powder (Cho & Lee ).…”
Section: Discussionmentioning
confidence: 99%
“…Propolis has been successfully used as a growth enhancer and immuno-modulator in several fish species (Abd-El-Rhman, 2009;Deng et al, 2011;Bae et al, 2012). Research has correlated its capacity as a growth enhancer to its antimicrobial, anti-parasitic, and immune-stimulant properties (Meurer et al, 2009;Segvic-Bubic et al, 2013;Uczay et al, 2014), although to our knowledge, no studies have investigated the effect of propolis on fish morphology and muscle gene expression.…”
Section: Introductionmentioning
confidence: 99%